Strategi Komunikasi Foodgram dalam Konten Review Kuliner Di Instagram TV - Firmansyah Firmansyah; Ida Ri'aeni; Rizki Budhi Suhara (JIKA (Jurnal Ilmu Komunikasi Andalan), 2021)
The Instagram account @kulinercirebon is one of the foodgrams that presents various kinds of culinary information which is quite famous among Cirebon culinary hunters, many people use it to find recommendations for places to sell food or drinks in Cirebon with a number of followers reaching 163,000 Instagram users (March 2021) targeting viewers from among the people of Cirebon and tourists from outside Cirebon who are looking for a culinary place for food and drinks. Communication strategies are very important for the development of culinary review video content on Instagram social media, the strategies used in content are used to attract the number of followers and viewers. This research is qualitative which aims to analyze using Harold D. Lasswell's communication theory and use swot analysis to analyze the strengths, weaknesses, opportunities, and threats in the communication strategy used by the @kulinercirebon instagram account.The data collection method that the author uses in this study is the interview method as the main method, while other methods that support to complete this research use the method of observation and documentation.The conclusion in this study is that the role of the @kulinercirebon instagram account is as a medium for disseminating information about recommendations for culinary places to communicants to increase sales of companies or culinary business actors who have collaborated to advertise through the @kulinercirebon instagram account. In formulating a strategy, it is quite interesting so that the contents in the Instagram content can be easily understood by the audience so that it can influence the attitude of the audience who are interested in visiting and trying the culinary that he has recommended. In promoting culinary places in culinary review video content using Instagram TV, because Instagram TV is considered more effective in showing videos because in its use it is better and maximal.